Penentuan Nilai Aset Dan Metode Depresiasi Aset SMA Muhammadiyah 3 Jember Berbasis Nilai-Nilai Keislaman - Aspirandi, Rendy Mirwan; Thamrin, Mohammad; Satoto, Eko Budi; Halim, Moh; Sahida, Ayunda Septia Wulandari; Wulandari, Dwi Agustin (Abdi Panca Marga, 2023)
Assets are the most important part of an entity, both private and state entities (Sarikadarwati et al., 2022). Asset data owned by an entity becomes the basis for assessing the development of the entity concerned. Assets are also the basis for determining the size of an entity. In fact, SMA Muhammadiyah 3 Jember has not optimally implemented asset recording. Therefore, determining the value of assets and the method of depreciating assets is needed by SMA Muhammadiyah 3 Jember. This community service method is carried out online and offline (blended learning). The mentoring process takes about 6 months. The result of the dedication is that the asset officers of SMA Muhammadiyah 3 Jember understand the method of valuation of assets and depreciation that are treated for each asset at SMA Muhammadiyah 3 Jember. The asset valuation method used is based on acquisition cost. The depreciation or depreciation method used is the straight-line method which is relatively simple and easy to understand. The economic age of Muhammadiyah 3 Jember High School assets is based on tax regulations Regulation of the Minister of Finance of the Republic of Indonesia Number 11/PMK.010/2020 concerning Income Tax Facilities for Investment in Certain Business Fields and/or in Certain Regions.